First Results of Integrated Geoarchaeological Analyses in the Capua Territory (Campania, Italy) - Elda Russo Ermolli; Nicola Busino; Fabio Marzaioli; Concetta Rispoli; Ettore Valente (Geosciences)
This study employs a multidisciplinary approach, integrating geoarchaeology, geomorphology, archaeometry, and palynology to analyze settlement patterns and land use in the surroundings of Capua (southern Italy) during the medieval transition. Borehole sampling and stratigraphic studies indicate significant landscape transformations due to human activity, particularly deforestation and agricultural expansion. Radiocarbon dating confirms settlement activity from antiquity through the early medieval period. Results suggest that Capua’s elevated position provided natural flood protection, influencing its continuous habitation. Pollen analysis reveals a shift from forested landscapes to open pastures, indicating intensive land use. Future research will focus on refining the chronology and archeological context of this transition, further clarifying Capua’s historical and environmental development.